Response of speargrass (Imperata cylindrica) to cover crops integrated with handweeding and chemical control in maize and cassava - Chikoye, David; Manyong, Victor M.; Carsky, R.J.; Ekeleme, F.; Gbehounou, G.; Ahanchédé, A. (Elsevier, 2002)
Speargrass [Imperata cylindrica (L.) Raeuschel] is a noxious weed widespread in most tropical zones of the world. Studies were conducted in the savannah of West Africa from 1997 to 1999 to evaluate crop yield, speargrass control, and net benefit from the use of cover crops integrated with handweeding and chemical control in maize and cassava. Glyphosate and handweeding were main treatments. Subplot treatments were type of cover crop [velvetbean, Mucuna cochinchinensis (Lour.) A. Chev., kudzu, Pueraria phaseoloides (Roxb.) Benth, and velvetbean intercropped with kudzu] and plots without cover crops. Weeding five times or applying glyphosate was more effective than weeding twice in preventing crop yield losses and suppressing speargrass. Plots that received glyphosate or those weeded five times had 28–59% higher crop yields than plots weeded twice at all locations. In maize, subplots without cover crop had 30% more maize grain yield than plots with cover crops. In cassava, subplots without cover crops at Ezillo and plots where kudzu was intercropped with velvetbean at Ogoja had the lowest cassava tuber yields. Speargrass was more effectively suppressed in plots with cover crops than in plots without cover crops. Across all main treatments, velvetbean nearly eliminated rhizomes of speargrass within 2 years of treatment application at Avrankou. It was cheaper to use glyphosate than handweeding for speargrass control in both crops. Cover crops generally gave better economic benefit in cassava while in maize an opposite trend was observed.